Fifty years of surgery for pancreatic cancer - Hackert, Thilo; Klaiber, Ulla; Pausch, Thomas; Mihaljevic, André Leopold; Büchler, Markus W. (Pancreas, 2020)
The surgical treatment of pancreatic cancer (PDAC) has seen sweeping changes during the past 5 decades. Up to the middle of the 20th century resection rates were below 5%, but the numbers of curative resections for PDAC are now continuously increasing due to improved neoadjuvant treatment concepts as well as progress in surgical techniques and perioperative management. During the same period, mortality rates after pancreatic surgery have decreased considerably and are now less than 5%. One of the most important cornerstones of reduced mortality has been the concentration of PDAC surgery in specialized centers. In addition, the management of postoperative complications has improved greatly as a result of optimized interdisciplinary teamwork. Adjuvant chemotherapy has become the reference treatment in resected PDAC, achieving significantly prolonged survival. Moreover, the concept of borderline resectable PDAC has emerged to characterize tumors with increased risk for tumor-positive resection margins or worse outcome. The best treatment strategy for borderline resectable PDAC is currently under debate, whereas neoadjuvant therapy has become established as a beneficial treatment option for patients with locally advanced PDAC, enabling conversion surgery in up to 60% of cases. This review article summarizes the principal changes in PDAC surgery during the past 50 years.
Gesehen am 24.09.2020